1996
DOI: 10.1111/j.1399-302x.1996.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a protease from Streptococcus oralis C104

Abstract: Streptococcus oralis is among the earliest colonizers of the tooth surface during plaque formation. As such, its enzymatic activities may influence ecologic succession on the tooth surface. In the current study, we use zymograms and preparative polyacrylamide gel electrophoresis to identify and purify a protease from S. oralis (sanguis) C104. Proteases from S. oralis C104 were detected in cell pellets at 133, 146 and 176 kDa as clear proteolytic bands on gelatin-substrate zymograms. Preparation of the major (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…). Aprotinin is a commonly used serine protease inhibitor (Lo & Hughes, ; Park et al ., ). Iodoacetamide and EDTA are used as cysteine and metalloprotease inhibitors, respectively (Jankiewicz & Bielawski, ; Keller et al ., ; Yin et al ., ; Hassanein et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Aprotinin is a commonly used serine protease inhibitor (Lo & Hughes, ; Park et al ., ). Iodoacetamide and EDTA are used as cysteine and metalloprotease inhibitors, respectively (Jankiewicz & Bielawski, ; Keller et al ., ; Yin et al ., ; Hassanein et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…4). Aprotinin is a commonly used serine protease inhibitor (Lo & Hughes, 1996;Park et al, 2012b). Iodoacetamide and Co-isolation with S. epidermidis, protease production of S. epidermidis (the average absorbance per CFU mL À1 is given) and the ability of S. aureus to form biofilms (evaluated by CV staining) are also given.…”
Section: Effectmentioning
confidence: 99%
“…Microbial proteinases can also inactivate important host immunedefence molecules, such as immunoglobulins (von PawelRammingen & Björck, 2003), proteins of the complement system (Chen & Cleary, 1990) and antimicrobial peptides (Schmidtchen et al, 2002;Sieprawska-Lupa et al, 2004;Thwaite et al, 2006). Moreover, several species of oral streptococci produce extracellular proteinases capable of degrading albumin (Lo & Hughes, 1996), immunoglobulin A (Plaut et al, 1974) and salivary proteins (Choih et al, 1979). Many bacteria-derived proteinases cleave human kininogens, resulting in the release of kinins, potent proinflammatory peptides (Herwald et al, 1996;Imamura et al, 2005;Scott et al, 1993; for a review see Imamura et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S. gordonii is well known to colonize endothelial surfaces, especially damaged heart valves, in cases of infective endocarditis (15). Extracellular proteases produced by oral streptococci have been shown to degrade host proteins including albumin (24), salivary proteins (4), casein (28), and gelatin and collagen (14). It has been suggested that such proteases enable nutrient acquisition during times of stress or slow growth, as is seen within the bacterial vegetation causing endocarditis or within biofilms (17).…”
mentioning
confidence: 99%